Comparative Analysis of Salivary Glutathione Reductase Levels in Smokers and Non-Smokers with Periodontitis Following Non-Surgical Periodontal Therapy - Vaishali Mashalkar (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study investigates the impact of smoking on oxidative stress and the response to non-surgical periodontal therapy (NSPT) in individuals with periodontitis, focusing on salivary glutathione reductase (GR) levels as a biomarker. We compared 50 smokers and 50 non-smokers, assessing periodontal parameters and GR levels at baseline and six months post-therapy. Smokers exhibited significantly lower baseline GR levels (4.5 ± 0.8 U/mL) compared to non-smokers (6.2 ± 1.1 U/mL), indicating higher oxidative stress. Following NSPT, both groups showed significant improvements in periodontal health, with non-smokers experiencing greater gains: probing depth reduced by 21.7% in non-smokers and 18.5% in smokers, clinical attachment level improved by 21.1% and 16.7%, bleeding on probing decreased by 30.8% and 28.6%, and plaque index reduced by 30.4% and 24.0%, respectively. GR levels increased by 44.4% in smokers and 43.5% in non-smokers, suggesting reduced oxidative stress post-therapy, though improvements were more pronounced in non-smokers. These findings highlight the need for personalized periodontal care, emphasizing oxidative stress management and smoking cessation support to enhance treatment outcomes. Further research should explore additional biomarkers and antioxidant therapies to optimize periodontal therapy in smokers.